Comparison of viewpoints of health care professionals with or without involvement with formal ethics processes on the role of ethics committees and hospitals in the resolution of clinical ethical dilemmas. (March 2015) - Marcus, Brian S; Carlson, Jestin; Hegde, Gajanan G; Shang, Jennifer; Venkat, Arvind
Objective: Our objective was to evaluate whether those individuals with previous involvement with formal clinical ethics processes differ in their attitudes towards the resolution of prototypical clinical ethics cases than general health care professionals. We hypothesized that those individuals with previous participation in ethics consultation would have significantly different attitudes on the appropriate role of ethics committees in the assessment and resolution of clinical ethical dilemmas than those who have not. Methods: We conducted a case-based survey of health care professionals at six US hospitals. We administered the survey to health care professionals in a variety of clinical roles at each center and further sub-categorized these by respondents reporting or not reporting their membership on an ethics committee or participation as an ethics consultant/requestor of ethics consult services. Using the analysis of variance test, we present the variation in attitudes using a 5-point Likert scale with 95% confidence intervals and significance set at p ≤ 0.05. Results: A total of 240 respondents completed the survey (response rate: 63.6%) from all six surveyed centers (128 respondents with involvement with ethics consultation, 112 respondents without). Health care professionals not previously involved with formal clinical ethics processes were less likely to view the ethics committee as having a role in resolving the presented clinical ethical dilemmas ( p = 0.01 for analysis of variance comparison). Conclusion: In this multi-center survey study, health care providers without previous involvement with formal clinical ethics processes were less likely than those with previous involvement to support a role for ethics committees aiding in ethical case resolution.